Upaya Digitalisasi melalui Pendampingan Pembuatan Akun Instagram untuk Usaha UMKM Kopi Heloo - Bintang, Abbin Mutiara; Rahmadan, Noval Syabirin; Alfajri, Octo; Peranata, Suria; Hasanah, Uswatun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Digitalization is crucial for MSMEs as key drivers of the local economy. This study explores how assisting the "Heloo" coffee MSME in creating an Instagram account enhances digital presence. Activities include account creation, content management, and marketing strategies. Guidance covers effective use of Instagram features, hashtags, and customer engagement. Results show improved brand exposure, increased followers, and active interaction, especially among youth. Feedback also helps improve product quality. This mentoring proves that social media use can strengthen MSME competitiveness and market reach. The study may serve as a reference for MSMEs and policymakers to support broader digital adoption.Moreover, the mentoring process not only provided technical support but also increased the owner's confidence in managing digital tools independently. Consistent posting schedules, story updates, and interactive content such as polls and Q&A sessions contributed to higher engagement rates. Collaborations with local influencers and participation in online campaigns further expanded visibility. The initiative also included basic training in graphic design and copywriting to help the MSME create appealing content. As a result, Heloo Coffee began receiving more online orders and inquiries, indicating a shift toward digital sales channels. Overall, the project underscores the transformative power of social media in modern MSME development.